2005
DOI: 10.1080/01463370500090332
|View full text |Cite
|
Sign up to set email alerts
|

Are We Violating Their Expectations? Instructor Communication Expectations of Traditional and Nontraditional Students

Abstract: For years, researchers have been telling teachers how to communicate with students. Advising them to be immediate, clear and engage in affinity-seeking behaviors has been based on traditional undergraduate student responses. Adult education scholars recognize age and experience create unique expectations for instructors and the learning environment. Utilizing Expectancy Violations Theory, an investigation of traditional and nontraditional students' prescriptive expectations and experiences with instructor nonv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…Jay and Janschewitz (2008) argued that ''taboo words' most potent emotional quality is arousal'' (p. 271) and Jay, Caldwell-Harris, and King (2008) concluded that it was the arousal associated with taboo words that made them memorable. Existing research on expectancy violations has distinguished between expectations of what is likely to occur (i.e., predictive expectancies) and what should occur (i.e., prescriptive expectancies) and has examined prescriptive expectancies in the contexts of student expectations of college instructors (Houser, 2005) and expectations about affection communicated by nonromantic partners (Floyd & Morman, 1997). Prescriptive expectancies should also be relevant in the context of swearing.…”
Section: Theoretical Explanation For Perceptions Of Swearingmentioning
confidence: 97%
“…Jay and Janschewitz (2008) argued that ''taboo words' most potent emotional quality is arousal'' (p. 271) and Jay, Caldwell-Harris, and King (2008) concluded that it was the arousal associated with taboo words that made them memorable. Existing research on expectancy violations has distinguished between expectations of what is likely to occur (i.e., predictive expectancies) and what should occur (i.e., prescriptive expectancies) and has examined prescriptive expectancies in the contexts of student expectations of college instructors (Houser, 2005) and expectations about affection communicated by nonromantic partners (Floyd & Morman, 1997). Prescriptive expectancies should also be relevant in the context of swearing.…”
Section: Theoretical Explanation For Perceptions Of Swearingmentioning
confidence: 97%
“…Communication research suggests that immediacy can influence athletes' perceptions of coaches (Haselwood et al, 2005), students' perceptions of teachers (Punyanunt-Carter & Wagner, 2005), and even student effectiveness (Houser, 2005). Yet, while Sparrowe and Liden's work suggests that task-related immediacy will not allow a high LMX relationship to form, this body of communication theory suggests that followers associate immediacy with a more positive and supportive relationship.…”
Section: Speed/pacementioning
confidence: 98%
“…Moreover, student perceptions of an instructor's communication competence positively influences cognitive learning (Wrench & Punyanunt, 2004). For appropriateness, the classroom maintains numerous interaction rules known and practiced by both students and teachers (e.g., raising hand to speak) (Burgoon, 1995;Houser, 2005). The context of any classroom is unique, thus perceptions of appropriateness and effectiveness of certain behaviors vary from classroom to classroom: ''A given sequence of communication behaviors may be perceived to be competent in one context (relational, chronological, environmental, etc.…”
Section: Review Of Literaturementioning
confidence: 99%